Architects at work - Films for the Humanities & Sciences (New Jersey : Films for the Humanities & Sciences, 2006)
This compilation of recent'NewsHour' segments introduces viewers to Frank Gehry, Rem Koolhaas, Daniel Libeskind, Vincent Scully, and Elizabeth Plater-Zyberk, visionaries in the world of architecture.
Originally produced as segments of the television program The News hour with Jim Lehrer in 2006.
Host, Jim Lehrer.
DVD format.
Keywords: Gehry, Frank O., -- 1929- -- Interviews; Scully, Vincent, -- 1920- -- Interviews; Koolhaas, Rem -- Interviews; Libeskind, Daniel, -- 1946- -- Interviews; Plater-Zyberk, Elizabeth -- Interviews; Architects -- Interviews; Architecture, Modern -- 21st century